Migration of EEG Spike Foci and Epilepsy Outcome - J Gordon Millichap (Pediatric Neurology Briefs)
Researchers at Chung Shan Medical University, Taichung, and other centers in Taiwan analyzed 969 EEGs from 463 children with epilepsy to determine outcome differences over 3 years between those with fixed epileptic foci and those with migrated foci.